The Influence Of Location And Word Of Mouth On Purchasing Decisions (Survey on Ayam Petelur Armina Consumers) - Pratama, Muhammad Agung Noor; Askolani; Lestari, Suci Putri (Journal of Management, Economic, and Accounting, 2024)
The purpose of this study was to determine the effect of location and word of mouth on purchasing decisions at Ayam Petelur Armina. The research used is quantitative research with a survey method to 100 respondents of Ayam Petelur Armina consumers who live in Tasikmalaya City. The types of data used are primary data and secondary data. The data analysis technique uses multiple linear regression analysis. The results of this test prove that location and word of mouth have a significant effect simultaneously and partially on purchasing decisions at Ayam Petelur Armina.